Evaluation of nutrition knowledge and dietary intake of male academy rugby union players undertaking a nutrition education program. Issue 15 (10th November 2011) - Tester, E; Sutton, L; Duckworth, L
Abstract : The aim was to determine if the implementation of a nutrition education program can improve the nutritional knowledge and dietary practice of male academy rugby union players. On obtaining institutional ethics approval, 16 players were recruited and split by age category. Both an under 16 (U16) group N=9 (17 ± 1 y) and under 19 (U19) group N=7 (19 ± 0 y) participated in an eight session program. The sessions informed participants on the principles of sports nutrition and met individual nutrition needs. Both groups completed a nutrition knowledge questionnaire and a 7 day diet diary pre and post program delivery. Dietary analysis was conducted and adequacy of intake was assessed by comparison with calculated recommended values. Delta values were used to assess the difference between required and actual intake values for different dietary components. Results show increases in nutrition knowledge scores for all participants, 31.5–37.2 (p=0.000). There was a strong positive correlation between age and nutrition knowledge scores both pre (r=0.518, n=18, p<0.027) and post (r=0.472, n=18, p<0.48). There was improvement in energy and carbohydrate intake within the U19 group, t (6) = −3.837, p<0.009, t (6) = −4.653, p<0.003 respectively. Although not significant, improvements in fluid intake were seen as average intakes increased by 1.72 l (U19) and 0.68 l (U18). The main finding was improvements in nutrition knowledge following a nutrition education program. A link between age and knowledge was highlighted. There were improvements in dietary intake whereby participants more closely met recommended intakes. For the U19, improvements were statistically significant, but for the U18 who are not solely responsible for their dietary intake improvements were less evident. Further research into the barriers facing younger athletes in achieving adequate dietary intake is warranted.